A scalable highly thermal conductive silicone rubber composite with orientated graphite by pre-vulcanizing and multilayer stacking method. (June 2022) - Zhang, Rong; Liu, Zhuohang; Sun, Zhijian; He, Xuehang; Lin, Qianhui; Xiang, Yifan; Fang, Xiang; Li, Siqi; Fu, Xudong; Liu, Qingting; Hu, Shengfei; Ping Wong, Ching
Abstract: Silicone rubber (SR)-based thermal conductive composites is a good candidate for heat-resisted thermal interface materials (TIM). It's a challenge to increase thermal conductivity (TC) and get thick sample as the difficulty of vulcanizing SR in core layer. Herein, a highly thermal conductive and 10 mm SR/graphite (Gr) with oriented Gr (O-SR/Gr) was prepared by pre-vulcanization and multilayer-stacked hot pressing. A well cured thick composite with dense structure and excellent orientation of Gr was obtained. The in-plane TC of O-SR/Gr reached 13.93 W/(m·K) with 66.67 wt% Gr, while the samples without pre-vulcanization presented voids among sample. The dense composite and excellent orientation of Gr reduced interfacial thermal resistance (ITR) as fitted by Foygel model. They also presented rapid warming rate during actual warming process and remarkable heat resistance till 200 °C. The finding might provide inspiration for efficient design of high thermal conductivity composites on large scale.